Effects of sevoflurane anaesthesia on postoperative executive function and visual memory - Zainal Abidin, Huda (2015)

(untitled)
Introduction: Over the last decade, the perioperative morbidity and mortality has been dramatically improved. POCD still represent one of the major adverse events particularly involving the elderly patients. The exact causes of POCD are still uncertain and believed to be multifactorial. It is unknown whether it is the results of surgery or anaesthesia itself. Studies done on regional and general anaesthesia failed to find any difference whether any of these method contribute to POCD. Reports showed that POCD causing more persistent problem and prolonged cognitive disturbance compared to delirium (Bryson GI et al., 2006). Furthermore, certain study reported that postoperative patients especially when it involved the elderly patients can extend up to 6 months and even beyond. Objectives: To determine the effects of sevoflurane on postoperative cognitive function namely executive function and visual memory. Methodology: Patients who scheduled for orthopaedic surgery and fulfilled the inclusion criterias were included. A total number of 37 patients with male: 28 female: 9 were enrolled in this study. This is a prospective observational study; all of the datas were collected from Hospital Universiti Sains Malaysia. The same investigator assessed the neurocognitive function of the patients preoperatively and postoperatively. We decided to take 24 to 48 hours postoperatively as we assumed the effects of anaesthetic drugs already subsided. The neurocognitive assessment was done using CANTAB, ISO 2006 recommended tool. Thedemographic data collected included age, gender, race, ASA classification, and duration of surgery. Where else the data taken from the CANTAB battery included Big Little Circle (BLC), Intra/extradimensional Set Shift (IED), and Delayed Matching to Sample (DMS). Results: The reports that we had from all the three tests performed by patients were all directed towards no impairment in cognitive function postoperatively. When compared BLC results postoperatively, patients showed significant improvement with the reaction time with 32 patients completed test successfully and p number obtained was (p<0.05). The number of errors made in IED test declined and number of stages completed increased. IED Completed stage Errors mean 5.1. (p<0.05), IED Completed Stage Trials mean 8.595 and (p<0.05), IED EDS Error mean of 6.595 and (p<0.05) and IED total errors mean of 5.945 and (p<0.05). Same goes with the DMS test where patient’s memory was tested. DMS Mean Correct latency showed significant improvement postoperatively with mean of 566.13 and (p<0.05). There were no correlations noted between all these tests with patient’s age, gender, education level, race or even duration of surgery. Conclusion: Sevoflurane anaesthesia does not cause postoperative cognitive impairment in healthy, young adult population.